Study The Structural and Optical Properties of Silver Nanoparticles Prepared By Using Pulsed Laser Nd-YAG - Sahib N. Abdul Wahid, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Silver nanoparticles were prepared by using Nd-YAG pulse laser with (ï¬=1064 nm), and the optical properties of these nanoparticles were studied. Then the optical absorbance spectrum measurements in NaOH were carried out. Shape, size and concentration of the colloid silver AgNPs show a spherical shape and a particles diameters in the range of (30-50) nm. Finally, the spectral measurements such as surface plasmon emission (SPE) from the prepared silver nanoparticles were done.